Vacancy filling effect in thermoelectric NbO. (2nd March 2015) - Music, Denis; Geyer, Richard W; Bliem, Pascal; Hans, Marcus; Primetzhofer, Daniel
Abstract: Using density functional theory, we have systematically explored the 1 a and 1 b vacancy filling in NbO (space group Pm -3 m ) with Nb and N, respectively, to design compounds with large Seebeck coefficients. The most dominating effect was identified for filling of 1 b Wyckoff sites with N giving rise to a fivefold increase in the Seebeck coefficient. This may be understood based on the electronic structure. Nb d —nonmetal p hybridization induces quantum confinement and hence enables the enhancement of the Seebeck coefficient. This was validated by measuring the Seebeck coefficient of reactively sputtered thin films. At 800 °C these electrically conductive oxynitrides exhibit the Seebeck coefficient of −70 µ V K −1, which is the largest absolute value ever reported for these compounds.